Severe pneumonia caused by Chlamydia abortus complicated by hemophagocytic syndrome: a case report - Xu, Jisong; Zeng, Haiwen; Li, Huangen; Lin, Xiaoyun; Lin, Tianlai (Frontiers in Medicine, 2025)
BackgroundPneumonia caused by Chlamydia abortus (C. abortus) is uncommon, particularly when complicated by severe acute respiratory distress syndrome (ARDS) and multiple organ dysfunction syndrome (MODS). Hemophagocytic lymphohistiocytosis (HLH) is a rare and potentially fatal disease characterized by the uncontrolled activation and non-malignant expansion of macrophages and T lymphocytes. This report describes a case of severe pneumonia complicated by hemophagocytic lymphohistiocytosis, caused by Chlamydia abortus.Case introductionA 42-year-old female with no history of underlying medical conditions, no known exposure to poultry or avian animals, and no consumption of undercooked sheep or ewes contaminated with infected placenta, presented to the respiratory medicine department with a 3-day history of fever, cough, and sputum production. Initially diagnosed with community-acquired pneumonia, she was treated with piperacillin-tazobactam for 5 days. However, despite 12 h of high-flow oxygen therapy, her oxygenation did not improve, and she was transferred to the ICU, where she received additional treatments, including moxifloxacin and methylprednisolone. Her condition worsened further, prompting the initiation of veno-venous extracorporeal membrane oxygenation (VV-ECMO) and bronchoalveolar lavage for metagenomic next-generation sequencing (mNGS) analysis. The mNGS results identified Chlamydia abortus with a count of 180,791, leading to the cessation of moxifloxacin and the addition of omadacycline to her regimen. After 13 days of ECMO therapy, her condition improved, and the ECMO was discontinued. The endotracheal tube was successfully removed 15 days after intubation. However, 3 days later, the patient developed recurrent fever, pancytopenia, elevated ferritin, blood lipids, soluble CD25, and decreased natural killer cell activity, leading to a diagnosis of hemophagocytic lymphohistiocytosis (HLH). She was treated with ruxolitinib, etoposide, and other supportive medications. Despite treatment, her condition continued to deteriorate. Three days later, the family opted to discontinue therapy due to financial constraints. She passed away 12 h later.ConclusionChlamydia abortus infection can result in severe acute respiratory distress syndrome (ARDS), necessitating prompt diagnosis and active clinical intervention. This case is unique due to the rare occurrence of HLH following Chlamydia abortus infection, a pathogen not commonly associated with this condition. Metagenomic next-generation sequencing (mNGS) offers a distinct advantage in rapidly and accurately identifying rare pathogen infections, while extracorporeal membrane oxygenation (ECMO) can be an effective treatment for severe pneumonia caused by Chlamydia abortus. It highlights the importance of early recognition and management of HLH in patients with severe, unexplained infections, particularly in those with unusual pathogens. Additionally, Chlamydia abortus infection may be complicated by HLH. Clinicians should remain vigilant for patients presenting with unexplained high fever, hepatosplenomegaly, and pancytopenia, and HLH screening should be initiated promptly. Early intervention can significantly improve patient survival rates.